Association of TGF‐β1 −509C/T, +869T/C, and +915G/C polymorphisms with periodontitis susceptibility. (19th December 2014) - Huang, J; Ding, C; Chen, X; He, R; Chen, N
<x xml:space="preserve">Abstract</x> Objectives To investigate the potential association of TGF‐β1 −509C/T (rs1800469), +869T/C (rs1800470), and +915G/C (rs1800471) polymorphisms with susceptibility to periodontitis. Materials and Methods Several electronic databases were searched for eligible articles. Odds ratios (ORs) along with their 95% confidence intervals (CIs) were calculated to assess the strength of relationship between the TGF‐β1 polymorphisms and periodontitis risk. Results Eleven studies were searched without any language restriction. Pooled estimates showed that TGF‐β1 −509C/T polymorphism was associated with decreased risk of periodontitis. Subgroup analysis revealed that −509C/T T allele was associated with decreased risk of chronic periodontitis (CP) in Asians (T allele vs C allele: OR = 0.81, 95% CI = 0.69–0.97, Pheterogeneity = 0.25). Furthermore, the +915G/C CC genotype might be associated with elevated risk of CP in Caucasians (CC vs GG: OR = 9.14, 95% CI = 1.01–82.50, Pheterogeneity = 0.49). Concerning +869T/C polymorphism, no evidence of significant association was identified. Conclusion This meta‐analysis suggested that TGF‐β1 −509C/T T allele was associated with decreased risk of CP in Asians, while +915G/C CC genotype might contribute to increased CP risk in Caucasians. Replication studies of our results in independent large populations are necessary to validate this association in diverse populations.